DESCRIPTION OF THE RESULT OF RHEUMATOID FACTOR IN MENOPAUSAL WOMEN IN SIDORAME BARAT II VILAGE ZONE VI MEDAN PERJUANGAN DISTRICT - Siregar, Ice Ratnalela (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
Menopause is a condition that occur in women with thedecreasing hormone who affect on menstruationcycle to the lower level that make the menstruation can not happend again. Decreasing hormon can be oneof the triggers of Rheumatoid Arthritis that caused by decreasing the imunity who make an autoimunereaction. One of the checks that can be a reference tho detect the Rheumatoid Arthritis is RheumatoidFactor. Rheumtaoid Factor using aglutination principle between sheep erythrochytes which been fixedwith human sera. The type of research that has been used is descriptive with 26 samples who get fromlemeshow formula. Sera used as the material and research held at imuno-serology’s LaboratoriumPolytechnic of Health, Health Analyst Major Department of Medicine Medan. The purpose of this studyis to determine the Rheumatoid Factor description result on menopausal women. The result who has beenheld show there are 10 samples that obtained positive (39%) and 16 samples who obtained negative result(61%)